2018
DOI: 10.1021/acs.jpcb.8b07259
|View full text |Cite
|
Sign up to set email alerts
|

Solvent Quality Controls Macromolecular Structural Dynamics of a Dendrimeric Hydrogenase Model

Abstract: We report a spectroscopic investigation of the ultrafast dynamics of the second-generation poly(aryl ether) dendritic hydrogenase model using two-dimensional infrared (2D-IR) spectroscopy to probe the metal carbonyl vibrations of the dendrimer and a reference small molecule, [Fe(μ-S)(CO) 3 ] 2 . We find that the structural dynamics of the dendrimer are reflected in a slow phase of the spectral diffusion, which is absent from [Fe(μ-S)(CO) 3 ] 2, and we relate the slow phase to the quality of the solvent for pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 75 publications
0
1
0
Order By: Relevance
“…Vibrational relaxation and thermalization in molecules occur via an intramolecular vibrational energy redistribution (IVR) process, which has been studied using a variety of experimental methods. Energy transfer and thermalization in covalent networks is better understood than the transfer across a metal center in a transition-metal complex for which only a few studies were reported. The coordination bonds at the metal center are often weak resulting in very inefficient energy transfer across the metal. For example, the lifetime of CO stretching modes in some metal carbonyls reaches 1 ns. A similar situation is encountered when an organic compound is attached to a metal or semiconductor surface. The surface binding energy is often small resulting in weak thermal conductivity through the interface. In contrast to surfaces, transition-metal complexes feature high-frequency vibrational modes on each side of the metal atom, which can potentially participate in the exchange of high-frequency quanta across the metal center.…”
Section: Introductionmentioning
confidence: 99%
“…Vibrational relaxation and thermalization in molecules occur via an intramolecular vibrational energy redistribution (IVR) process, which has been studied using a variety of experimental methods. Energy transfer and thermalization in covalent networks is better understood than the transfer across a metal center in a transition-metal complex for which only a few studies were reported. The coordination bonds at the metal center are often weak resulting in very inefficient energy transfer across the metal. For example, the lifetime of CO stretching modes in some metal carbonyls reaches 1 ns. A similar situation is encountered when an organic compound is attached to a metal or semiconductor surface. The surface binding energy is often small resulting in weak thermal conductivity through the interface. In contrast to surfaces, transition-metal complexes feature high-frequency vibrational modes on each side of the metal atom, which can potentially participate in the exchange of high-frequency quanta across the metal center.…”
Section: Introductionmentioning
confidence: 99%